In Vitro Anti-Viral Effects of Small Heat Shock Proteins 20 and 27: A Novel Therapeutic Approach - Vahabpour, Rouhollah; Soleymani, Sepehr; Roohvand, Farzin; Zabihollahi, Rezvan; Bolhassani, Azam (Current Pharmaceutical Biotechnology, 2019)
Background: The protective effects of heat shock proteins (Hsps) were studied in some infectious and non-infectious diseases, but their specificity was slightly known in various disorders. Among Hsps, small Hsps (e.g. Hsp27 and Hsp20) have important roles in protein folding and translocation, and also in immunity. Methods: In this study, overexpression of Hsp20 and Hsp27 was performed by transfection of the plasmids encoding Hsp20 and Hsp27 (pEGFP-Hsp20 and pEGFP-Hsp27) into Huh7.5, Hela and Vero cells using Lipofectamine along with heat shock. Then, their anti-herpes simplex virus-1 (HSV-1), anti- human immunodeficiency virus-1 (HIV-1) and anti-hepatitis C virus (HCV) effects, as well as cytotoxicity, were evaluated in vitro, for the first time. Results: Our data showed that simultaneous treatment with Lipofectamine and heat shock augmented the rate of transfection and subsequently the expression of Hsps in these cells. Moreover, overexpression of Hsp20 in HCV-infected Huh7.5 cells, HIV-infected Hela cells and HSV-infected Vero cells reduced the replication of HCV, HIV and HSV, respectively. In contrast, overexpression of Hsp27 significantly decreased HSV replication similar to Hsp20, but it did not affect the replication of HIV and HCV. Conclusion: Generally, Hsp20 was identified as a novel anti-HCV, anti-HSV and anti-HIV agent, but Hsp27 was efficient in the suppression of HSV infection. These Hsps may act through suppression of virus entry and/ or through interaction with viral proteins. Thus, it is necessary to determine their exact mechanisms in the near future.
Keywords: HCV